Economic analysis of public investment in alternative agricultural water management schemes: A case study from northern Ghana - Balana, Bedru; Akudugu, Mamudu A. (Informa UK Limited, 2023)
This study assesses the institutions and economics of public investments in three agricultural water management infrastructure and technologies: rehabilitation of small reservoirs, fuel-powered motorized small pumps and electricity-powered large pumps. We find that all three technologies yield positive returns on investment, but their applicability varies spatially and across community due to differences in capital costs and environmental feasibilities or conditions. Sensitivity analyses indicate the base decision parameters – net present value, benefit–cost ratio and internal rate of return – remain stable despite potential changes in the flow of future benefits or costs. This provides further evidence about the worthiness of investment in irrigation infrastructure and technologies. However, significant under-utilized infrastructural capacities exist that warrant complementary investment in human and institutional capacities. Based on the findings policy recommendations are provided.